2013
DOI: 10.1002/anie.201303875
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Analysis, and Properties of [8]Circulenes

Abstract: Polygons: [8]Circulenes were easily prepared by Pd-catalyzed annulations of tetraiodotetraphenylenes with alkynes. Their saddle-shaped structure with an [8]radialene character was identified by X-ray crystallography. Similar to 1,3,5,7-cyclooctatetraene, they have a tub-shaped eight-membered ring, but all of the bond lengths and bond angles are almost equal. Variable-temperature NMR investigations showed interesting dynamic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 37 publications
6
126
0
1
Order By: Relevance
“…[8]circulene ([8]C) 30 , tetraoxa [8]circulene (4O [8]C) 31 and tetrathio [8]circulenes 20 have been synthesized and their X-ray structural data are available in literature. Several theoretical research groups reported 14-18, 20, 22, 32 structures and properties of these [8]circulenes using the B3LYP functional and similar basis sets considered herein and results are in accordance with experimental findings.…”
Section: Resultsmentioning
confidence: 99%
“…[8]circulene ([8]C) 30 , tetraoxa [8]circulene (4O [8]C) 31 and tetrathio [8]circulenes 20 have been synthesized and their X-ray structural data are available in literature. Several theoretical research groups reported 14-18, 20, 22, 32 structures and properties of these [8]circulenes using the B3LYP functional and similar basis sets considered herein and results are in accordance with experimental findings.…”
Section: Resultsmentioning
confidence: 99%
“…10). 132 Octaaryl- [8]circulene 44 could be obtained in remarkable 60-75% yields, corresponding to B88-93% for each annulation step, allowing the preparation of several hundred milligrams of 44.…”
Section: Synthesis Of Graphene Moleculesmentioning
confidence: 99%
“…For instance, [8]circulene 5 H , which was synthesized as late as in 2013, 9 was studied in detail by quantum chemical methods at different levels of theory 40 ± 42 10 years prior to its successful synthesis, and the calculated shape and structural parameters proved to be consistent with the X-ray diffraction data 9 (circulene 5 H is a simpler analogue of compounds 5 containing no methyl and aryl substituents, the cyclic structure of which was correctly predicted to have a saddle-shaped form with D 2d symmetry). 40 ± 42 The structure and some energy properties of quadrannulene 4 were also predicted 43 shortly before the first synthesis 8 of this bowl-shaped representative of benzocirculenes in 2010.…”
Section: Iv1 Hypothetical Heterocirculenesmentioning
confidence: 99%